Direito à educação escolar: limites e possibilidades rumo à efetivação do paradigma da proteção integral de crianças e adolescentes - Lizana, Inês Júlia de Oliveira (Universidade do Vale do Rio do Sinos, 2009)
In the International Convention on the Rights of the Child, of November 20, 1989, children and adolescents have, in their capacity as citizens and with all their due rights, the international legal statute of this new conception, that establishes a new paradigm: the Paradigm for the Full Protection of Children and Adolescents. Changes have been taking place in every sphere of Brazilian society to ensure the effectiveness of the provisions agreed upon, but these same provisions do not yet allow us the full and complete execution of these guaranteed rights. Education as a Fundamental and Social Right, guaranteed and protected under the new Paradigm, is beset by the same contradictions encountered in the execution of Human Rights, as a whole, and especially as they affect children and adolescents in our country. The Right to Education is guaranteed as a Fundamental Right in the 1988 Brazilian Constitution and through infraconstitutional legislation; and its importance has been recognized in international documen
Keywords: autonomia; educação; fraternidade; cidadania; autonomy; education; fraternity; citizenship; Ciências Sociais Aplicadas